PERFORMA PRAGMATIK ANAK USIA TIGA TAHUN DARI BERAGAM LATAR BELAKANG SOSIAL - Yesika Maya Ocktarani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2013)
In our society, child language development is usually identical with the amount of new vocabularies produced by a child. Yet, in preparing a child to get involved with his or her community, parents should also consider childs pragmatic competence. This paper is aimed to give perspective about childrens pragmatic competence particularly on their performance in Directive Speech Acts (DSA) and also to describe their environment which supports their pragmatic performance. Using qualitative descriptive method, researcher involves four children who have different social background. Direct observation is used in order to get data naturally and it is also completed by in-depth-interview with childrens parent and teacher. The result shows that 3-year-old children are able to understandand to produce DSA. Their ability in understanding DSA can be seen when they respond ones DSA, both verbally and non-verbally. In producing DSA, they use indirect form to express their intention. Another result of this research is that children should have linguistic environment to stimulate their ability in using language as tools of communication. The more children interact verbally with a speech community, the better their pragmatic competence will be.Keywords: Directive Speech Acts, three-year-old children, linguistic environment